Pengaruh Return On Equity dan Debt to Equity Ratio Terhadap Audit Delay - Filistian, Vindy; Wenny, Cherrya Dhia (Universitas Multi Data Palembang, 2024)
This study is intended to examine the application of return on equity and debt to equity ratio to audit delay of property and real estate sector companies. Secondary data were used for this study. The sample selected used purposive sampling so that the sample obtained was 81 company samples. Data testing using the help of SPSS 26 application. The results of this study show that return on equity and debt to equity ratio have a negative and significant influence on audit delay.